O computador e a internet como instrumentos de aprendizagem nas salas de recurso - Buniotti, Daniel (2014)
Considering the school as an environment conducive to building any knowledge at all, the theme of this study is the computer and the internet used as tools to facilitate the learning of students who attend the multifunctional hall I, also known as Living Resources (SR). The objective is to analyze the pedagogical possibilities of the internet and computer teachers working in Multifunction I rooms, pointing out how technology can be very suitable in school , thus easing the learning gaps of students that attend . To do so, we performed a literature search on authors who advocate the use of computers and the Internet in the school environment as a result sought to be understood by reading official documents from the Secretary of State of Paraná Education (SEED) as the operation of multi-purpose resources , who intended these rooms and also a field research conducted through a questionnaire administered to ten teachers who work in resource rooms of three state establishments from Paraná, with questions related to use of computer and the internet as a facilitator of learning. Finally, suggestions for how to use the Internet and computer learning of students attending multifunctional room features 1. Through this research it appears that although schools analyzed, have a multifunctional well structured with technological devices such as tablet, laptop, desktop computer, digital camera, plasma TV and broadband internet access, room teachers do not use as a methodological tool. It follows therefore, that there is need to encourage and empower these professionals for use of technological media, considering that the teaching work of multi-functional features to be fully differentiated from the common school class.